L’Italia che non vota: dinamiche e propagazione spazio-temporale dell’astensionismo - Alessandra Ferrara; Giovanni Lombardo; Francesco Giovanni Truglia (QOE-IJES, 2023)
Abstentionism is also on the rise in Italy. Its significance, both politically and socially, is evidenced not only by the number of voters who did not go to the polls, but also by the territorial spread of the phenomenon. In this paper, the authors summarise the dynamics of the quantitative dimension of electoral abstention and, using an appropriate statistical-methodological instrumentation, through an analysis of the spatial-temporal propagation forms (spatial spillovers) they also highlight where this behaviour is most deeply rooted and how it has spread. The analysis on the overall dimension of the phenomenon is complemented by an in-depth exploration (in paragraph 2) that describes the weight of certain components of involuntary abstentionism. These, which are certainly less analysed than voluntary abstentionism, are treated in view of their growing potential as drivers of the phenomenon, as a consequence of both demographic dynamics and the evolution of specific social behaviour.